Engineered small extracellular vesicles loaded with miR-654-5p promote ferroptosis by targeting HSPB1 to alleviate sorafenib resistance in hepatocellular carcinoma - Jiao Sun; Qi Liu; Yanfang Jiang; Zhihui Cai; Hui Liu; Huaiwen Zuo (Cell Death Discovery, 2023)
Abstract Sorafenib (sora) is the initial therapy for patients with progressive hepatocellular carcinoma (HCC), but the emergence of drug resistance has seriously impacted its therapeutic efficacy. However, the mechanism of sora resistance remains unclear, and effective strategies to overcome drug resistance are still lacking. By establishing a sora-resistant hepatocellular carcinoma cell line, we found that Heat Shock Protein Family B (small) Member 1 (HSPB1) was markedly upregulated in sora-resistant HCC cells. Further research revealed that the ferroptosis resistance induced by HSPB1 upregulation plays a crucial role in sora resistance. In addition, we confirmed that miR-654-5p enhances sora-induced ferroptosis by binding to HSPB1 and reducing its protein levels. To enhance miRNA stability and delivery efficiency in vivo, we used small extracellular vesicles (sEV) derived from human adipose mesenchymal stem cells as miR-654-5p carriers, creating engineered sEV (m654-sEV). The research demonstrated that m654-sEV effectively delivers miR-654-5p to HCC cells, targeting HSPB1 and enhancing sora-induced ferroptosis. This improves therapeutic effects on sora-resistant HCC cells and xenograft tumors, restoring their sensitivity to sora. In summary, m654-sEV, which targets HSPB1 via miR-654-5p delivery, represents a promising strategy for addressing sora-resistant issue. The combined use of m654-sEV and sora has the potential to significantly enhance therapeutic efficacy for patients with sora-resistant HCC.